Esoteris-Mistik dalam Teks Pangujanan - Muhammad Heno Wijayanto; I Made Suparta (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2021)
Pangujanan is a Javanese-Bali text containing means and spells to making rain based on the local wisdom of Balinese culture. The aim of this research is to examine the esoteric and mystical aspects contained in the Pangujanan text. The theoretical basis used in this research is Philo-ethnography to reveal the esoteric and mystical in the Pangujanan text. The result is esoteric aspects that are prohibitive and guiding, as well as mystical aspects in the form of presenting the power of Iadewata 'Dewa Pujaan' to a practitioner through mentioning aspects of Iṣṭadewata, such as Kanda Mpat, Pañcaṛṣi, Catur Lokapala, Dewata Nawasanga, and Daśākṣara to bring down rain. The causality between esotericism and mysticism is that bringing Iṣṭadewata into the soul is secret and limited to certain circles. From the results of the analysis, it can be concluded that the esoteric-mystical aspect that involves God in it is a symbol that God's involvement in all aspects of life is still considered important. — Pangujanan merupakan teks berbahasa Jawa-Bali berisi sarana dan mantra untuk menurunkan hujan berdasarkan kearifan lokal budaya Bali. Penelitian ini mencoba menelaah aspek-aspek esoteris dan mistik yang terdapat dalam teks Pangujanan. Landasan teori yang digunakan dalam penelitian ini adalah filoetnografi untuk mengungkap esoteris dan mistik dalam teks Pangujanan. Hasilnya adalah aspek-aspek yang bersifat esoterik bersifat larangan dan tuntunan, serta aspek yang bersifat mistik berupa menghadirkan kekuatan Iṣṭadewata ‘Dewa Pujaan’ kepada seorang praktisi melalui penyebutan aspek-aspek dari Iṣṭadewata, seperti Kanda Mpat, Pañcaṛṣi, Catur Lokapala, Dewata Nawasanga, dan Daśākṣara untuk menurunkan hujan. Kausalitas antara esoteris dan mistik adalah menghadirkan Iṣṭadewata ke dalam jiwa bersifat rahasia dan terbatas untuk kalangan tertentu saja. Dari hasil analisis dapat disimpulkan bahwa aspek esoteris-mistik yang melibatkan Tuhan di dalamnya merupakan simbol bahwa keterlibatan Tuhan dalam segala aspek kehidupan masih dianggap penting.